Preditores de demora pré-hospitalar em doentes com enfarte agudo do miocárdio com elevação do segmento ST - Ribeiro, S (2010)
BACKGROUND: Early reperfusion therapy in ST-elevation myocardial infarction (STEMI) correlates with its success. The aim of our study was to characterize patients admitted with a diagnosis of STEMI with longer prehospital delay and to analyze its impact on the choice of treatment and on in-hospital prognosis. METHODS: We performed a retrospective cohort study of 797 patients consecutively admitted with a diagnosis of STEMI from January 2002 to December 2007. The cutoff for longer pre-hospital delay was defined as three hours. We analyzed demographic, clinical and echocardiographic data and determined the predictors of pre-hospital delay of > or = 3 h. RESULTS: Of the 797 patients, 77% were male and mean age was 62 +/- 13.64 years. Patients with longer pre-hospital delay were older (p < 0.001), with a higher proportion of female (p = 0.001), hypertensive (p = 0.002), diabetic (p < 0.001), and surgically revascularized patients (p = 0.007), and those with symptom onset between 10 pm and 8 am (p = 0.001). The group with shorter pre-hospital delay included more men (p = 0.001), patients with prior myocardial infarction (p = 0.025) and smokers (p = 0.009). Independent predictors of pre-hospital delay of 3 h included female gender (odds ratio [OR] 1.5, 95% confidence interval [CI] 1.03-2.16), diabetes (OR 1.78, 95% CI 1.23-2.56), systemic arterial hypertension (OR 1.41, 95% CI 1.04-1.93), and symptom onset between 10 pm and 8 am (OR 1.76, 95% CI 1.31-2.38). Independent predictors of pre-hospital delay of > or = 3 h included male gender (OR 0.67, 95% CI 0.46-0.97) and prior myocardial infarction (OR 0.48, 95% CI 0.27-0.84). Reperfusion therapy was performed in 72%, 52% and 12% of patients with pre-hospital delay of <3 h, 3-12 h and >12 h, respectively (p for trend <0.001). Patients with longer delay more often had severely reduced left ventricular ejection fraction (LVEF) (p = 0.004). A non-significant trend was observed towards increased in-hospital mortality with longer delay (8.3% vs. 6.6%, p for trend = 0.342). CONCLUSIONS: A significant proportion of patients continue to have long pre-hospital delay. Female patients and those with diabetes, systemic arterial hypertension and symptom onset between 10 pm and 8 am made up the majority of this group. Longer pre-hospital delay was associated with a lower probability of being treated with reperfusion therapy, a higher frequency of severely depressed LVEF and a non-significant increase in in-hospital mortality. It is essential to develop mechanisms to reduce pre-hospital delay.